Eventease: Design and Implementation of a GUI-Based Python Event Registration and Ticketing System with Sqlite Integration (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Efficient management of event registration and ticketing is crucial for the success of academic, corporate, and social events. Traditional manual methods, including paper-based logs and unintegrated spreadsheets, are prone to errors, duplicate entries, and operational delays, especially during high-volume registration periods. This study presents EventEase, a modern, GUI-based Event Registration and Ticketing System engineered using Python and integrated with a locally isolated SQLite relational database engine.The application utilizes advanced visual toolkits like ⁠customtkinter⁠ to deliver a professional user experience featuring real-time input normalization and an interactive data visualization backend powered by ⁠matplotlib⁠. Architecturally, the system separates roles into administrative control channels and customer booking gateways. Administrators have access to full event creation mechanisms supporting multi-tiered ticket rates (⁠Regular⁠, ⁠VIP⁠, ⁠Student⁠), granular category and venue configuration utilities, real-time attendee gate verification with explicit timestamp logging, and automated transaction backup systems running on Write-Ahead Logging (⁠WAL⁠) parameters. Simultaneously, the front-end customer client handles seamless profile creation, dynamic seat availability checks, cash-tender calculation wizards, and instant receipt generation.Functional testing confirmed that all database joins, user-role authentications, and reporting modules operate with zero record degradation. EventEase demonstrates how desktop applications can be built to optimize operational capacity, remove data redundancy, and secure transactional integrity within institutional environments.